The Great Stone Circle (B) at Grange, Co. Limerick: A Ceremonial Space for All Seasons? - Prendergast, Frank (Journal of Skyscape Archaeology, 2015)
Prehistoric stone circles are generally interpreted as having had a variety of roles and meaning in the Neolithic and Bronze Age, especially as places for gathering and ceremony in the case of the largest examples. This paper undertakes an archaeoastronomical investigation of one of the rarest types, known as an embanked stone circle. Contrary to popular belief, the findings do not indicate any clear evidence of significant astronomical alignments inherent in the monument’s architecture. However, the character of the Grange (B) stone circle is considered and interpreted within a broader range of perspectives including morphology, landscape setting, ritual function, and the likely role and meaning of the sky in the past. The modern perception of skyscapes as cultural heritage assets is considered in terms of their protection.